Yield and nutritional quality of nine summer annual forages - Kuhl, Gerry L.; Shroyes, J.P.; Hartman, Paul D.; Fjell, Dale L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Nine summer annual forages were studied to evaluate yield and nutritional quality differences resulting from forage type and cultivar when cut at two stages of maturity. Substantial dry matter yield and quality differences were observed among the six hybrid pearl millets tested. Several hybrid pearl millets gave comparable dry matter yields to the sorghum-sudans at boot and headed stages of growth. Hybrid pearl millets were much higher in crude protein than the hybrid sorghum-sudans and sudangrass. Although yield increased markedly between boot and headed cutting stages, nutritional value declined greatly. Nitrate levels were excessively high in all forages when harvested at the boot stage in July, and several were still above safe levels at the headed stage. Therefore, nitrate and feed quality testing is recommended for safe and efficient utilization of summer annual forages.
Keywords: Beef; Summer annuals; Pearl millet; Sudan; Yield; Forage quality; Nitrate